National Agricultural Resilience Framework - Vermeulen, Sonja J.; Abubakar Y; Conway, G.; Dziba L; Hoevel M; Ibe C; Ibrahim, A.; Olokor J; Ifeijka Speranza, Chinwe (2014)
Globally, agriculture is the mainstay of most well planned economies because it contributes significantly to the national GDP, creates employment, provides food for human sustenance, raw materials for industry and earns foreign exchange. Nigeria is blessed with tremendous agricultural resources spanning several agro-ecological zones. Nigeria’s total land area is 92.3 million ha with cultivable area estimated at 84 million ha, which is 91% of the total area. Forests account for 13% of the land area. Most of the country’s land area is fertile and conducive for growing a wide range of crops and raising livestock. Nigeria’s 853 kilometer coastline along the Gulf of Guinea is a gateway to a vast ocean which together with ample fresh water resources provided by the Niger and Benue river systems afford tremendous potential for fisheries and aquaculture/mariculture. Nigeria took advantage of these resources to establish itself as an agricultural powerhouse in the 1960s. According to statistics from the UN Food and Agricultural Organization (FAO), by 1961 the country accounted for 42% of the global trade in groundnut oil, 27% of the world’s palm oil industry and 18% of global trade in cocoa. The country was also self-sufficient in food production before the discovery of oil in the 1960s.